The Impact of Banks’ Economic Policies on the Intensification of Class Difference Case Study: Fifth to Eighth Governments (1989-2005) - Farhadi, Gholamali; Khoddamy, Alireza; Rezakarimi, Majid (International Journal of Psychosocial Rehabilitation, 2020)
One of the goals of the Islamic Revolution is to improve the distribution of incomes and reduce the class divide, but the course of affairs in various governments does not fit well with this ideal. From the beginning of the fifth and sixth governments, indicators such as the increase in the Gini coefficient show the trend of increasing income inequality and class gaps between different sections of society. The purpose of this study is to investigate the effect of banks’ economic policies on the intensification of class gap in the period 1989-2005. This research is a causal library and analytical study based on panel data analysis. Statistical data were purposefully selected as a sample size based on the statistics of the Central Bank and the Management and Planning Organization. In this research, to estimate the model, the vector autoregression method in Eviews software has been used. The results showed that, in addition to reducing GDP, rising inflation and liquidity in the studied states have exacerbated the class gap. In general, the results of the analysis indicated that government policies have affected the process of increasing the class gap, the main reason being the mismatch between inflation and rising incomes.